Severe cicatricial alopecia as a rare cutaneous side effect due to erlotinib - case report - Magdalena Żychowska; Aleksandra Batycka-Baran; Wojciech Baran; Joanna Maj (Termedia Publishing House, 2016)
Introduction . Epidermal growth factor receptor inhibitors (EGFRI) are commonly used in the treatment of solid tumors. Cutaneous side effects occur in 80% of patients and are the most frequent adverse events. However, cicatricial alopecia is a rarely described side effect of EGFRI. Objective . To present cutaneous toxicities in a patient treated with erlotinib and underscore cicatricial alopecia, rarely described in the literature. Case report. We present a 63-year-old woman diagnosed with non-small cell lung cancer and treated with erlotinib, who developed extensive papulo-pustular eruption with severe involvement of the scalp and cicatricial alopecia. Other adverse events included trichomegaly, paronychia, granuloma pyogenicum-like lesions, dryness of the skin and pruritus. Conclusions . Cicatricial alopecia in the presented patient may be a result of delayed introduction of dermatological treatment. Therefore, all dermatologists should be aware of treatment modalities of EGFRI-induced toxicities.